Principales enfermedades crónico degenerativas en el Hospital Básico José Miguel Rosillo de Cariamanga en el periodo enero - diciembre 2016. - Miñano Alzamora, Jhonatan Josué (2018)
According to the WHO (World Health Organization), chronic degenerative diseases are long-term and slowly progressive diseases, the main cause of death and disability in the elderly, being one of the main topics of interest in health. The objective of this study is to identify the main chronic degenerative diseases in patients over 60 years of age served in the ambulatory service of the José Miguel Rosillo de Cariamanga Basic Hospital in the period January - December 2016 and a proposal was prepared for the promotion of health and prevention of chronic degenerative diseases. The sample consisted of 2581 patients and a retrospective descriptive design was used. The technique that was applied for the collection of information based on quantitative techniques, through the collection of information and statistical data of the news and medical records. The results show that 60% of patients treated in this service have chronic degenerative diseases. In order of frequency, diabetes mellitus type 2 (32%), hypertension (28%), chronic bronchitis (22%), osteoarthritis (14%) and benign prostatic hypertrophy (4%) were found, constituting the five most frequent diseases in patients older than 60 years who attended this hospital center. Keywords: Elderly, chronic degenerative diseases